Application of Culturally Responsive Teaching Approach in Learning for Strengthening Global Diversity Character in Elementary School Learners - Wardani, Salsabella Kusuma; Utami, Ratnasari Diah (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe the process of applying the Culturally Responsive Teaching approach to strengthen the profile of Pancasila students in the dimensions of global diversity in students of SDN 09 Ngringo. Methodology: This type of research is descriptive qualitative research with data collection techniques of interviews, observation, and documentation. The data obtained were analyzed through three stages data reduction, data presentation, and conclusion drawing. Results: The results showed that the application of the Culturally Responsive Teaching (CRT) approach at SDN 09 Ngringo improved the dimensions of the global diversity Pancasila student profile. In the learning process, students can foster tolerance towards peers and teachers, be fair to peers, recognize cultural differences, actively participate in group discussions, and improve learning outcomes. Applications/Originality/Value: The impact of CRT implementation on global diversity character development, students gain a deeper understanding of their own culture and the culture of their peers. Teachers' challenges and barriers are teachers' lack of understanding of students' culture, limited material resources, challenges managing a diverse classroom, and lack of training and support for teachers.